Tomato carotenoid cleavage dioxygenases 1A and 1B: Relaxed double bond specificity leads to a plenitude of dialdehydes, mono‐apocarotenoids and isoprenoid volatiles. Issue 1 (25th June 2014) - Ilg, Andrea; Bruno, Mark; Beyer, Peter; Al-Babili, Salim
Abstract : The biosynthetic processes leading to many of the isoprenoid volatiles released by tomato fruits are still unknown, though previous reports suggested a clear correlation with the carotenoids contained within the fruit. In this study, we investigated the activity of the tomato ( Solanum lycopersicum ) carotenoid cleavage dioxygenase (SlCCD1B), which is highly expressed in fruits, and of its homolog SlCCD1A. Using in vitro assays performed with purified recombinant enzymes and by analyzing products formed by the two enzymes in carotene‐accumulating Escherichia coli strains, we demonstrate that SlCCD1A and, to a larger extent, SlCCD1B, have a very relaxed specificity for both substrate and cleavage site, mediating the oxidative cleavage of cis ‐ and all‐ trans ‐carotenoids as well as of different apocarotenoids at many more double bonds than previously reported. This activity gives rise to a plenitude of volatiles, mono‐apocarotenoids and dialdehyde products, including cis ‐pseudoionone, neral, geranial, and farnesylacetone. Our results provide a direct evidence for a carotenoid origin of these compounds and point to CCD1s as the enzymes catalyzing the formation of the vast majority of tomato isoprenoid volatiles, many of which are aroma constituents. Abstract : The substrate specificity and products of tomato carotenoid cleavage dioxygenases 1A and 1B were analyzed. New cleavage sites leading to new enzymatic products were identified. CCD1A and 1B link the carotenoid pattern of tomatoes to the many isoprenoid volatiles produced.